Psychosis Associated with Herbal Products: Iatrogenic Delusional Disorder - Machado, Ana Sofia; Dias-Amaral, Ana; Silva, Alzira; Grangeia, Rosa (Acta Médica Portuguesa, 2021)
Metabolic, toxic or structural brain changes may present as psychotic symptoms. Organic delusional disorders are characterized by the presence of delusional ideas with evidence of brain dysfunction. Iatrogenesis may be a cause of this dysfunction. We present a case of neuropsychiatric symptoms, including delusional disorder, secondary to the use of herbal products. The patient’s perception regarding the safety of natural products might result in an omission to report their use during clinical history taking, and thus its use should be actively questioned.